2021
DOI: 10.3389/fneur.2021.713794
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Forecasting Using a Novel Sub-Scalp Ultra-Long Term EEG Monitoring System

Abstract: Accurate identification of seizure activity, both clinical and subclinical, has important implications in the management of epilepsy. Accurate recognition of seizure activity is essential for diagnostic, management and forecasting purposes, but patient-reported seizures have been shown to be unreliable. Earlier work has revealed accurate capture of electrographic seizures and forecasting is possible with an implantable intracranial device, but less invasive electroencephalography (EEG) recording systems would … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 51 publications
(89 reference statements)
2
58
0
Order By: Relevance
“…For example, a reliable method for detecting counting seizures using mobile EEG would introduce the opportunity to pre-emptively modify treatment regimens or plan the optimal timing for diagnostic studies. 74 Repeated long-term at-home recordings could allow seizure forecasting, and identification of seizures pattern and cycles, [75][76][77][78] which may enable a better understanding of the individual seizure risk over time and improve patients' quality of life. 79,80…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reliable method for detecting counting seizures using mobile EEG would introduce the opportunity to pre-emptively modify treatment regimens or plan the optimal timing for diagnostic studies. 74 Repeated long-term at-home recordings could allow seizure forecasting, and identification of seizures pattern and cycles, [75][76][77][78] which may enable a better understanding of the individual seizure risk over time and improve patients' quality of life. 79,80…”
Section: Discussionmentioning
confidence: 99%
“…In connection with an external recorder (the 24/7 EEG TM SubQ) combined with a complete data infrastructure and analytics software, the implanted electrode provides continuous (24/7) and automated electrographic seizure detection for up to 15 months (358)(359)(360). Several similar subscalp systems have been developed and tested in humans, including the use of such systems for seizure forecasting (359,361). The size of the subcutaneous needle electrode or subscalp device of the UNEEG system would be ideally suited for continuous EEG recordings in epileptic dogs, which we plan to explore soon.…”
Section: Epileptic Dogs As a Model For Novel Implantable Eeg Devicesmentioning
confidence: 99%
“…Another example is the Chronic Migraine Epidemiology and Outcomes (CaMEO) study, which assessed barriers to good medical care for chronic migraine [4]. Of 1,254 included patients, only <5% with chronic migraine traversed the 3 barriers -medical consultation, accurate diagnosis, and minimal pharmacologic treatment-to receiving proper care.…”
Section: Overarching Themementioning
confidence: 99%
“…Results of an open-label study with 263 migraine patients suggested that sTMS may be an effective, well-tolerated treatment option for migraine prevention [4]. A very recently published open-label study suggests that sTMS may be an effective, well-tolerated treatment option for the long-term prevention of difficult-to-treat, high-frequency episodic migraine and chronic migraine [5].…”
Section: Targeting Cortical Activation By Transcranial Magnetic Stimu...mentioning
confidence: 99%
See 1 more Smart Citation